The Use of Animated Film Media to Improve the Ability of Writing Short Stories in Elementary School - Nanda Saputra; Irnie Victorynie; Syarifah Rahmi; Syarifah Siregar; Dina Komalasari; Suhendi Syam (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research originated from the low skills of grade IV SDN (public school) 1 Sigli students in writing short stories. Learning media to write short stories is an alternative means of delivering material to students through animated film media. This study aims to determine the improvement of short story writing skills using animated film media in fourth grade students of SDN 1 Sigli. This research is a classroom action research (CAR) which was conducted in three cycles. Each cycle consists of four stages, namely planning, implementing, observing, and reflecting. The subjects of this study were 24 students of grade IV SDN 1 Sigli, consisting of 12 female students and 12 male students. The data collection technique was done by using tests, observations, and field notes. The data analysis used was a comparative descriptive analysis technique. The results of data analysis showed that the acquisition of student learning outcomes with an average value in cycle I: 60%, cycle II: 80%, and cycle III: 91%. Thus it can be concluded, the use of animated film media can improve students' short story writing skills, and teachers always improve their skills in using instructional media. This can be seen from the cycles obtained by students in each cycle.